Hubungan Kompetensi Guru dengan Hasil Belajar IPS di Sekolah Menengah Atas - Shinta Candra Karnaningsih; Sulton Sulton; Arafah Husna (Universitas Negeri Malang, 2021)
Abstract: This study aims to determine the relationship of social studies teacher competencies with student learning outcomes in Tulungagung High School. Teacher competence is a matter to support teaching and learning activities. Where a learning outcome can be improved through competent teachers. Learning outcomes are the learning achievements achieved by students in the process of teaching and learning activities. The data was obtained through secondary data from social studies teachers (Economics, Geography, History and Sociology) conducted by Tulungagung High School, namely Gondang High School, Pakel High School, PGRI High School, and Al Azhar Islamic High School. Hypothesis test results in this study obtained the results of a correlation of 0.792 and p = 0.00 <0.05. So the correlation coefficient is so high that there is a reliable relationship. So there is a relationship between the competence of social studies teachers with learning outcomes in Tulungagung High School. This study gets results if the competency of the teacher is high, so the learning outcomes achieved by the students also increase.Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan kompetensi guru IPS dengan hasil belajar siswa di Sekolah Menengah Atas Tulungagung. Kompetensi guru adalah suatu hal untuk mendukung kegiatan belajar mengajar. Dimana suatu hasil belajar dapat ditingkatkan melalui guru yang berkompeten. Hasil belajar adalah prestasi belajar yang diraih siswa dalam proses kegiatan belajar mengajar. Data didapatkan melalui data sekunder guru IPS (Ekonomi, Geografi, Sejarah, dan Sosiologi) yang dilaksanakan SMA Tulungagung yaitu Sekolah Menengah Atas Gondang, Sekolah Menengah Atas Pakel, Sekolah Menengah Atas PGRI, dan Sekolah Menengah Atas Islam Al Azhar. Hasil uji hipotesis dalam penelitian ini diperolah hasil korelasi 0,792 dan p = 0,00 < 0,05. Sehingga koefisien korelasi sangat tinggi bahwa ada hubungan yang bisa diandalkan. Sehingga ada hubungan antara kompetensi guru IPS dengan hasil belajar di Sekolah Menengah Atas Tulungagung. Penelitian ini mendapatkan hasil jika kompetensi yang dimiliki oleh guru tinggi, maka semakin meningkat pula hasil belajar yang dicapai oleh siswanya.